The ethics & poetics of alterity in Asian American poetry - Zhou, Xiaojing, 1952- (University of Iowa Press, 2006)
Poetry by Asian American writers has had a significant impact on the landscape of contemporary American poetry, and a book-length critical treatment of Asian American poetry is long overdue. In this groundbreaking book, Xiaojing Zhou demonstrates how many Asian American poets transform the conventional "I" of lyric poetry - based on the traditional Western concept of the self and the Cartesian "I"--To enact a more ethical relationship between the "I" and its others. Drawing on Emmanuel Levinas's idea of the ethics of alterity - which argues